2015
DOI: 10.1007/s10815-015-0495-1
|View full text |Cite
|
Sign up to set email alerts
|

Lack of carbon air filtration impacts early embryo development

Abstract: Purpose To assess human fertilization and preimplantation embryo development in the presence and in the absence of carbon filtration Methods This is a retrospective cohort analysis of fresh, controlled ovarian hyperstimulation cycles as well as previously cryopreserved pronuclear stage embryo transfer cycles in a single IVF center. Embryo development and cycle-based outcomes were compared among three groups: 1) when carbon filtration was present, 2) when carbon filtration was absent, and 3) when carbon filtrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
2
19
0
1
Order By: Relevance
“…Filtering the air to remove particulate matter and harmful chemicals [in particular volatile organic compounds (VOCs)] has been shown to increase the number of embryos that are of high morphological quality, develop to the blastocyst stage and result in live birth. [225][226][227][228] Because it would be unethical to intentionally expose human embryos to air pollutants to determine their effect, much of the existing evidence is from circumstantial retrospective studies, but animal studies have demonstrated a direct effect of VOCs on the embryo's ability to develop into blastocyst. 229,230…”
Section: Air Qualitymentioning
confidence: 99%
“…Filtering the air to remove particulate matter and harmful chemicals [in particular volatile organic compounds (VOCs)] has been shown to increase the number of embryos that are of high morphological quality, develop to the blastocyst stage and result in live birth. [225][226][227][228] Because it would be unethical to intentionally expose human embryos to air pollutants to determine their effect, much of the existing evidence is from circumstantial retrospective studies, but animal studies have demonstrated a direct effect of VOCs on the embryo's ability to develop into blastocyst. 229,230…”
Section: Air Qualitymentioning
confidence: 99%
“…In a retrospective cohort study of 2015, Munch et al 11 analyzed assisted reproduction cycles. The embryo development and the results based in the cycles were compared between three groups: 1) when there was carbon filtration; 2) when there was not carbon filtration; 3) when the carbon filtration was restored.…”
Section: Assisted Reproductionmentioning
confidence: 99%
“…The deleterious effects of poor air quality to embryo development and implantation and how controlling laboratory air quality can minimize such effects have been investigated over the last 15 years ( Table 1 ). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 Recognizing the importance of laboratory air quality to the safety of IVF treatments, regulatory directives in the European Union and Brazil dictate specific requirements for air quality control within reproductive laboratories. 18 19 Such regulatory directives aim to safeguard public health in line with the precautionary principle, but they require different strategies to mitigate the air-related risks (revised in Esteves and Bento, 2013).…”
Section: Importance Of Laboratory Air Quality To Embryo Development mentioning
confidence: 99%